Improvement Growth Root Plant Kesum (Polygonum minus) in System Hydroponics with various Potassium Concentration - Imam Alfiza Margolang; Risnawati; Yaseer Suhaimi bin Mohd Mohd (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
The Kesum plant, scientifically known as Polygonum minus, is a herbaceous species native to Southeast Asia (Malaysia, Indonesia, Vietnam, Thailand) that thrives in damp, waterlogged environments, such as the edges of ditches and lakes. This study aims to investigate the effect of potassium concentration on root growth of Kesum (Polygonum minus) plants grown in a floating raft hydroponic system. The experiment was conducted at the MARDI Greenhouse in Serdang, Selangor, Malaysia, employing a Randomized Block Design (RBD) with five potassium concentration treatments (0, 50, 100, 150, and 200 mg/L) and five replications. Kesum cuttings, each 15 cm in length, were planted in hydroponic containers measuring 1 m × 3 m × 0.3 m, with the nutrient solution adjusted to a pH of 5.5–6.5 and electrical conductivity (EC) of 2.0–2.5 mS/cm. Observed parameters included plant height, stem diameter, canopy area, SPAD value, fresh weight, dry weight, root fresh weight, root dry weight, and root length. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a significance level of 0.05. Results indicated that a potassium concentration of 150 mg/L yielded the highest fresh root weight (31.15 g) and optimal root length (22.31 cm), while a 100 mg/L potassium concentration supported the greatest plant height (82.77 cm). This study offers practical recommendations for farmers and agrotechnologists to apply potassium concentrations of 100-150 mg/L in hydroponic Kesum cultivation to achieve optimal root and vegetative growth and enhance production yields.